The WID‐qEC test: Performance in a hospital‐based cohort and feasibility to detect endometrial and cervical cancers. Issue 6 (1st October 2022) - Schreiberhuber, Lena; Herzog, Chiara; Vavourakis, Charlotte D.; Redl, Elisa; Kastner, Christine; Jones, Allison; Evans, Iona; Zikan, Michal; Cibula, David; Widschwendter, Peter; Pfau, Karin; Math, Barbara; et al.
Abstract: The majority of endometrial and cervical cancers present with abnormal vaginal bleeding but only a small proportion of women suffering from vaginal bleeding actually have such a cancer. A simple, operator‐independent and accurate test to correctly identify women presenting with abnormal bleeding as a consequence of endometrial or cervical cancer is urgently required. We have recently developed and validated the WID‐qEC test, which assesses DNA methylation of ZSCAN12 and GYPC via real‐time PCR, to triage women with symptoms suggestive of endometrial cancer using ThinPrep‐based liquid cytology samples. Here, we investigated whether the WID‐qEC test can additionally identify women with cervical cancer. Moreover, we evaluate the test's applicability in a SurePath‐based hospital‐cohort by comparing its ability to detect endometrial and cervical cancer to cytology. In a set of 23 cervical cancer cases and 28 matched controls the receiver operating characteristic (ROC) area under the curve (AUC) is 0.99 (95% confidence interval [CI]: 0.97‐1.00) with a sensitivity and specificity of 100% and 92.9%, respectively. Amongst the hospital‐cohort (n = 330), the ROC AUC is 0.99 (95% CI: 0.98‐1) with a sensitivity and specificity of 100% and 82.5% for the WID‐qEC test, respectively, and 33.3% and 96.9% for cytology (considering PAP IV/V as positive). Our data suggest that the WID‐qEC test detects both endometrial and cervical cancer with high accuracy. Abstract : What's new? While abnormal vaginal bleeding is a presenting symptom of endometrial and cervical cancers, only a small proportion of women who present with vaginal bleeding have endometrial or cervical cancer. Currently, the tests used to triage women with abnormal bleeding, such as ultrasound or cytology, are subjective and have modest accuracy. Here, the authors demonstrate that a real‐time PCR‐based test, which assesses DNA methylation at three gene regions using a cervical or vaginal sample, is able to identify 100% of women who have cervical or endometrial cancer with a high specificity (>80%), irrespective of the sample collection system.